Are Differences in Empathy Age-Related? - Paulus, Christoph M. (International Journal of Learning and Development, 2024)
In this study we wanted to show how different the mean values of the four empathy components Empathic Concern, Perspective Taking, Fantasy, and Personal Distress are in a total of 7 age groups between 15 and over 60 years old. Using questionnaire data from the German version of the Interpersonal Reactivity Index of a total of 9 156 subjects, we were able to show that, with the exception of the variable Fantasy, the youngest group in particular consistently exhibited the weakest expressions, and although the respective mean values differed significantly in some cases, the deviations were very small. Thus, we refute the assumption that empathy decreases with increasing age and were able to show that especially the affective components show a high stability. Finally, we advise against the formation of a total score on empathy because of the unclear diagnostic interpretability.